Proyecto de factibilidad para la instalacion de una guarderia en la ciudad de cuenca, canton Cuenca, provincia del Azuay. - Guncay S., Digna (2010)
This research was developed in the Southern Region of the country, aiming at presenting a proposal for implementing a service care and education of children. The introduction is a brief analysis of the situation of our province and region as it relates to the provision of such services. Then in the Materials and Methods are presented for information gathering techniques and research methods that helped us to present the results of this work. In the market research survey was applied to 399 families in the city of Cuenca, was determined that there is a demand, in terms of the service we offer is provided by fourteen companies dedicated to such activities in the area, which not meet demand. On the Project Engineering presents the process flow service with all its phases;in terms of size and location, the attached map of the physical layout of the plant. Also states that the company will be located in a central area of the city. The study presents the financial investment and financing, as well as indicators of the project financial evaluation, which determines that it is advisable to implement this undertaking. Regarding the administrative organization, has thought of a company Limited Liability Company, by the favorable conditions presented by this type of company.